Anti-cancer efficiency of natural killer cells differentiated from human adipose tissue-derived mesenchymal stem cells and transfected with miRNA150 - Karlitepe, A.; Kabadayi, H.; Vatansever, S.; Gurdal, M.; Gunduz, C.; Ercan, G. (Experimental Oncology, 2017)
Aim: The aim of this study is to investigate the effects of miR150 transfection on NK-like cells differentiated from adipose tissue derived mesenchymal stem cells (AD-MSCs). Methods: NK-like cells were differentiated from AD-MSCs and activated by miR150 transfection. Transfected/non-transfected NK-like cells were characterized by immunohistochemical and RTPCR analyzes. Apoptotic efficiency of the transfected/non-transfected NK-like cells on pancreatic cancer cells PANC1 were determined by TUNEL and RT-PCR. Results: In miR150-transfected cells, the increased expression of NK cell-specific genes such as GZMB, KIR2DL2, CD16, CD56, NKG2D, NKp46 and increased immunoreactivity of NK cell-specific surface marker CD314 (NKG2D) were evident. TUNEL assays showed that NK-like cells with/without transfection induced apoptosis in PANC1 cells in the same manner. The decrease in oncogene expression and the increase in the tumor suppressor gene expression in PANC1 cells upon co-culture with NK-like cells differentiated from AD-MSCs were more prominent following miRNA150 transfection. Conclusion: It was shown in vitro that NK-like cells could be obtained by differentiation from AD-MSCs and their efficiency could be increased via miR150 transfection. The results are encouraging for further clinical studies in improvement of immunotherapeutic approaches for cancer therapy.